Ownership, Competition, and Corruption : Bribe Takers versus Bribe Payers - Clarke, George R. G.; Xu, Lixin Colin (World Bank, Washington, DC, 2013)
Over the past few years, many studies have looked at the macroeconomic, cultural, and institutional determinants of corruption. This study complements these cross-country studies by focusing on microeconomic factors that affect bribes paid in a single sector of the economy. Using enterprise-level data on bribes paid to utilities in 21 transition economies in Easter Europe and Central Asia, the authors look at how characteristics of the firms paying bribes (such as ownership, profitability, and size) and characteristics of the utilities taking bribes (such as competition and utility capacity) affect the equilibrium level of corruption in the sector. On the side of bribe payers, enterprises that are more profitable, enterprises that have greater overdue payment to utilities, and de novo private firms pay higher bribes. On the side of bribe takers, bribes paid to utilities are higher in countries with greater constraints on utility capacity, lower levels of competition in the utility sector, and where utilities are state-owned. Bribes in the utility sector are also correlated with many of the macroeconomic and political factors that previous studies have found to affect the overall level of corruption.